2015
DOI: 10.3138/jcfs.46.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Normative, Structural, and Individual Factors that Predispose Adult Children to Provide Social Support to Their Elderly Parents

Abstract: This study is based on a face-to-face survey, conducted in 2009, with a representative sample of adults who were aged 45 years or above, living in the urban area of Santiago, Chile. This survey examined the exchange network between adults and their elderly parents, focusing on two of the main explanatory approaches to supportive family interrelations. That is, the norms of filial obligation and reciprocity. The article also investigates factors associated with the structure of needs and opportunities, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…There was high consistency in findings on the influence of children's financial resources on transfers to parents. Children's income or financial resources were positively associated with financial transfers [5,13,25,45,51,58,61,72], instrumental transfers [19,32,45], emotional transfers [45], and overall support [32]. Brandt (2013) [19] revealed that the higher the children's income, the more likely children provided help of all types to parents.…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was high consistency in findings on the influence of children's financial resources on transfers to parents. Children's income or financial resources were positively associated with financial transfers [5,13,25,45,51,58,61,72], instrumental transfers [19,32,45], emotional transfers [45], and overall support [32]. Brandt (2013) [19] revealed that the higher the children's income, the more likely children provided help of all types to parents.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Many studies investigated the relationship between the older generation's demographic factors (e.g., age, gender, marital status, education) and upward transfers from the younger generation. Most studies suggest that transfer receivers' age was positively related to financial transfers [1,2,11,15,51,67,78], instrumental transfers [1,2,5,15,19,23,28,35,37,43,51], emotional transfers [2,67,68], and overall transfers [27,31,48,58,62,75]. However, Albuquerque (2014) [10] found little impact of age on the probability of older people's receiving money.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…Answer options ranged from 1 ( not very well ) to 5 ( very well ). Considering the proportion of those with two surviving parents was less than three-fourths, getting along well with their father or mother was viewed as emotional closeness (very well, so well, well) and other options (neither well nor poorly, poorly) were viewed as non-emotional closeness (Lorca & Ponce, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Most Western studies indicate the prominence of geographic proximity and emotional closeness (Hogan et al, 1993; Schwarz, Trommsdorff, Albert, & Mayer, 2005) but do not take into account the role attitudes toward filial piety play in affecting intergenerational transfer due to the lack of cultural norms. A study indicated that the non-significant association between the filial obligation norm and support provided to parents in the Latin American population may be attributable to the fact that attitudes of filial obligation lose influence in more individualized societies (Lorca & Ponce, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation